The acute immune response to exercise: what does it mean? - Gabriel, H.; Kindermann, W. (International Journal of Sports Medicine, 1997)
The purpose of this article is to provide information about the exercise-induced alterations of cellular immune parameters depending on the intensity related to the individual anaerobic threshold (IAT) and duration of exercise. Immunological parameters were differential blood counts (CD14, CD45), monocyte subpopulations (CD14, CD16), lymphocyte subpopulations (CD3, CD4, CD8, CD45RO, CD19, CD16, CD56, HLA-DR) and natural killer cells (CD3, CD16, CD56), oxidative burst activity of neutrophils, and phagocytosis of neutrophils (flow cytometry). The main results were: (a) "Moderate" exercise (duration < 2h at about 85% of the IAT corresponding to a lactate steady state at about 2 mmol.l-1, < 30 min at the IAT corresponding to a lactate steady state of 4 mmol.l-1) elicits lower changes in cell concentrations and hormonal responses than strenuous exercise [exhaustive exercise at 100% IAT or above; (exhaustive) long-term (> 2-3h) endurance exercise]. Similar investigations about cell functions to decide about the positive or negative nature of these observations will have to follow in the future. (b) The neutrocytosis following exercise is more dependent on the duration than on the intensity of exercise. Especially exercise sessions that lead to a strong incline of the adrenocorticotropic hormone, beta-endorphin and cortisol are associated with this neutrocytosis. (c) Neutrophils' function during the exercise-induced neutrocytosis indicated by phagocytosis and oxidative burst activity is unchanged or reduced following strenuous endurance exercise, whereas bacterial URTI leads to similar neutrophil counts but significantly increased cell activities indicating the diverse meaning of the leukocytosis in infections (primed cells, enhanced cell activity, stimulated defense mechanism) and following exercise (impaired cell function, suppressed defense mechanism). (d) Regular monocytes (early differentiation stage) are strongly recruited into the circulation during long-term aerobic exercise, whereas mature monocyte cell counts (premacrophages) increase most with highly intensive (an)aerobic exercise above the IAT. Infections induced a maturation from regular to mature monocytes as a response to the infectious antigenic stimulus, whereas exercise does not, indicating the diversity between change of cell counts and function. (e) Long-term endurance diverse meaning leads to increases of activated CD45RO+ T cells (memory cell phenotype) but compared to the incline of cell concentrations and activation levels (% HLA-DR+ T cells) during infections like infectious mononucleosis this effect is small indicating only minor effects on T cell function by exercise. The effect of single bouts of exercise on immune cell counts is large but the effects on the cell function is - i.e. compared to bacterial URTI - relatively small.